Ligation of patent ductus arteriosus in very low birthweight premature neonates. Issue 7 (July 1985) - Ghosh, P K; Lubliner, J; Mogilnar, M; Yakirevich, V; Vidne, B A
Abstract : The results of ligation of a patent ductus arteriosus in 30 premature neonates with a very low birth weight were analysed. The mean gestational age at birth was 27 weeks and the mean weight 811 g. Attempted closure of the ductus with indomethacin in 19 infants failed, though there was temporary closure in nine. Congestive heart failure was present in 29 and respiratory distress in 22 patients. Endotracheal intubation with assisted ventilation was necessary in all cases. The mean age at operation was 13.5 days and ductal ligation was performed in the intensive care unit under local anaesthesia supplemented with pancuronium and pethidine. There were no intraoperative deaths, but five infants died in hospital. There were seven late deaths. Eighteen survivors have been followed for a mean of 26.5 months. Early ligation of a patent ductus arteriosus in premature infants with a very low birth weight improved the cardiorespiratory state. Long term follow up showed good clinical progress in two thirds of the surviving group.